The establishment of a scientific field: The history of reindeer husbandry research in Sweden 1900-1970 - Lantto, Patrik (Rangifer, 2011)
The focus of this article is the development of reindeer husbandry research as a scientific field within thenatural sciences, 1900-1970. Up until after World War II, research within this field was mostly carried out by socialscientists, while it was given very limited attention within the natural sciences. From the late 1940s this changed, as interest in reindeer husbandry research grew and more academic disciplines became involved, and during the following decades the field became established. The article examines research initiatives focused on reindeer husbandry within the natural sciences during the first half of the 20th century, discussing the motives for these studies as well as why they did not lead to the establishment of a scientific field. It then turns to the development after World War II, analyzing why reindeer husbandry research was established so quickly, and how the field developed up until 1970, both nationally within Sweden and as a Nordic cooperation.